Study of the explosion load characteristics and structural response law under a cabin water mist environment: Experimental tests and simulations - Xiaobin Li; Ya Zhang; Yiheng Zhang; Hai Huang; Zhiping Wang; Xingxing Wu; Wei Chen (Defence Technology, 2025)
To investigate the explosion load characteristics and structural response law in a water mist environment in a cabin, explosion experiments are carried out. The weakening rates of the initial peak overpressure, quasistatic pressure and structural residual deflection increase with increasing working pressure of the water mist nozzle. Specifically, the weakening rate of the initial peak overpressure ranges from 7.8% to 31.0%, the quasistatic pressure weakening rate ranges from 29.2% to 41.0%, and the weakening rate of the center of the plate residual deflection ranges from 10.8% to 34.4% under the various working pressures of the nozzles. To further explore the effect of water mist explosion suppression, a method for three-dimensional numerical simulations of water mist weakening the explosion shock wave is established to explore the explosion load characteristics of the compartment and the bulkhead response law. On the basis of the dimension analysis method, empirical formulas are derived to predict the residual deflection thickness in the center of the bulkheads. These findings provide the fundamental basis for the application of water mist in anti-explosive protection.